Lung transplant: the Western Australian experience. Issue 11 (1st November 2018) - Dhillon, Sarbroop; McKinnon, Elizabeth; Wrobel, Jeremy; Lavender, Melanie; Lawrence, Sharon; Gabbay, Eli; Musk, Michael
Abstract: Background: The Western Australian lung transplant programme commenced in 2004 to serve the growing demand of patients with end‐stage lung disease. Aim: This report summarises our 11‐year experience in lung transplantation. Methods: Data on 115 consecutive patients and their respective donors transplanted between 2004 and 2015 were collected. The Kaplan–Meier method was used to estimate survival. Cox regression was used to analyse the impact of donor and recipient characteristics on survival. Results: A total of 88 bilateral, 22 single‐lung and 5 heart‐lung transplants were performed in Western Australia during the first 11 years of the lung transplant programme. The most common indications for transplantation were interstitial lung disease (30.4%), cystic fibrosis (27.8%) and chronic obstructive pulmonary disease (excluding alpha‐1 antitrypsin deficiency) (22.6%). Median recipient age was 50 years. Overall survival rates were 96% at 3 months, 93% at 1 year, 84% at 3 years and 70% at 5 years. Older age and higher BMI negatively impacted survival. Chronic lung allograft dysfunction was the leading cause of late mortality. Conclusion: Lung transplantation is a treatment option in end‐stage lung disease, with annual transplant rates in Western Australia continuing to rise. Our patients enjoy survival rates that compare favourably against international standards.